Trends among native- and foreign-origin workers in U.S. computer industries. - Otoiu, Adrian; Titan, Emilia (Monthly Labor Review, 2017)
The article highlights trends among native- and foreign-origin workers in U.S. computer industries from 1980 to 2014. Data provide shows the proportion of native- and foreign-born workers in the U.S. labor force, occupational specialization by place of origin, role of foreign-born workers in creative occupations in information technology (IT) industries, creative jobs in metropolitan areas with innovative IT clusters, and occupational structure of IT professionals in creative IT industries.